2015
DOI: 10.1038/ejcn.2015.209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional status and support in children with congenital heart disease

Abstract: Moderate or severe malnutrition is present in 15% of children with CHD, and it is more frequent in case of PH. Half of these children demonstrate low caloric intake, whereas few have proper nutritional support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 29 publications
2
69
1
4
Order By: Relevance
“…cyanotic infants with PH). Furthermore, in this study, the overall prevalence of malnutrition among infants with CHD was estimated at about 15%, which was lower than that in other similar studies (13).…”
Section: Discussioncontrasting
confidence: 84%
“…cyanotic infants with PH). Furthermore, in this study, the overall prevalence of malnutrition among infants with CHD was estimated at about 15%, which was lower than that in other similar studies (13).…”
Section: Discussioncontrasting
confidence: 84%
“…The prevalence of moderate to severe forms congenital heart defects is considered to be about 6 in 1000 live births (16, Figure 1. Malnutrition among the children compared with the WHO standards 17) and the incidence of moderate to severe forms of malnutrition in patients with congenital cardiac defects is 15%, more occurred in the presence of pulmonary hypertension (18), which the majority of them have low caloric intake and only a few have sufficient nutritional support (18). Several studies demonstrated that the total energy expenditure of the patients with non-corrected CHD is increased (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of malnutrition in children with congenital heart disease ranges between 15% and 64% . Many aspects of congenital heart disease put children at risk for malnutrition, including increased caloric needs, difficulties with adequate nutrition provision due to limitations secondary to ductal‐dependent disease and/or need for vasopressor support, increased risk of necrotizing enterocolitis, and fluid limitations.…”
Section: Congenital Heart Diseasementioning
confidence: 99%